Kindness and happiness at work - Oliver Scott Curry; Chloe San Miguel; Mehmet Necip Tunç (Discover Psychology)
Abstract What is the relationship between kindness and happiness at work? Previous research has shown that kindness is a cause and a correlate of happiness in general, and that kinder companies have happier employees. Here we build on this research by using a new measure—the The Kindness Questionnaire (KQ)—to look at the relationship between kindness to and from specific individuals at work, and workplace happiness. In Study 1 (n = 1151) we find that kindness to and from bosses, colleagues and subordinates, and a more general measure of kindness at work, predicts happiness at work. In Study 2 (n = 781) we find that kindness to bosses, colleagues and subordinates, and kindness from bosses, colleagues but not subordinates, as well as more general measures of kindness at work, predict happiness at work. However, in both studies, the simpler general measures of kindness at work are better predictors of happiness at work than the more complicated specific measures. We also find that fair pay, meaningful work, and a competent boss predict happiness at work. The implications, limitations and future directions of this research are discussed.